Current Evidence on Raw Meat Diets in Pets: A Natural Symbol, but a Nutritional Controversy - Yang Lyu; Caimei Wu; Lian Li; Junning Pu (Animals)
Feeding raw meat to cats and dogs has become a common practice in Western countries. Many pet owners cite their pets’ wild carnivore ancestry and believe raw meat diets are healthier, citing higher nutritional value, a lack of processing, low-carbohydrate content, and/or the presence of whole ingredients. However, due to the risks associated with raw meat-based diets (e.g., microbial contamination, nutritional imbalances) and growing concerns about food sustainability, most nutritional specialists and public health stakeholders question the practice of feeding raw meat. In this context, the vast majority of owners’ claims regarding the beneficial health effects of raw meat diets lack scientific substantiation, while professional advice primarily focuses on risks, often overlooking potential positive health effects. To better understand the effects of raw meat diets on the health of cats and dogs, this review summarises the latest scientific evidence and discusses both the potential health benefits and the risks associated with these diets.